Effects of two programs of metabolic resistance training on strength and hypertrophy - Carolina Brandt Meister; Felipe Augusto Tavares Kutianski; Larissa Carine Carstens; Sérgio Luiz Ferreira Andrade; André Luiz Félix Rodacki; Ricardo Martins de Souza
Abstract Introduction: The effects of low intensity resistance training combined with vascular occlusion have been investigated by several studies. Similar results on strength and hypertrophy have been observed when such method was compared to high intensity protocols. However, due to the specific apparatus needed to apply vascular occlusion (ex.: Kaatsu) on some exercises, alternative forms of metabolic training might be used. In the present study, an isometric contraction was performed within each concentric-eccentric transition phase, for every repetition, to elicit metabolic stress. Objective: The aim of the present study was to analyze the effects of two resistance training protocols with metabolic characteristics on strength (1MR), circumference (CIRC) and muscle thickness (measured with ultrasonography [MT]). Subjective perception of discomfort was also recorded with an analogical-visual pain scale (AVP). Methods: Twelve young, healthy men were trained with two different methods during 10 weeks. The right limb was trained with an isometric contraction within each concentric-eccentric transition phases for every repetition (ISO) whereas the left limb was trained with a pneumatic cuff to apply vascular occlusion (OC) on the knee extensor muscles. Both methods were trained at 20% 1MR. Results: It was observed increases on medial tight CIRC, proximal MT, medial MT, distal MT and 1MR, with no difference between both methods. The perception of discomfort was greater for ISO at the end of the third set and lower than reported by OC, at the beginning and end of the training program. Conclusions: Both protocols produced similar gains on strength and hypertrophy. The advantages of training with low loads are important to elderly or rehabilitation training programs. Other studies that compare this method with conventional resistance training are warranted.